Mathematical modeling of gas and gas condensate preparation unit with dynamic mode of low-temperature separation; Science, Technology and Higher Education - Dolganov I. M. Igor Mikhailovich; Pisarev M. O. Mikhail Olegovich; Dolganova I. O. Irena Olegovna; Ivashkina E. N. Elena Nikolaevna (2015, 2015)
Title screen